Comparative Perspective between TV community communication initiatives in Brazil and Spain: first notes - Vaz Cabral Filho, Adilson (2016)
This paper aims to investigate the engagement of community communication initiatives and their constitutive organizations in the regulatory process of digitization at different countries like Brazil and Spain. It is a comparative case study between these two countries, their differences and similarities of their political and cultural aspects that need to be highlighted: they’re at different moments of the transition to the digitalization of TV transmission; they have different structure and involvement from constituted organizations of community communication initiatives and have different and complex governments in regard to the proximity of community communication questions.